Development of electrospinning machine for the production of homogeneous and functionally graded multilayer polymeric nanofibers - Lim, Shing Chee (2022)
Electrospinning technology has been widely used in producing porous scaffolds consisting of nano- to microfibers. These porous electrospun scaffolds are useful in various applications including medical and filtration applications. The microstructure architecture such as pore size and fiber diameter is able to affect their function and efficiency. In medical applications, the control of pore sizes affects the environment to promote cellular activities. For filtration applications, the pore size can control filtration efficiency. The control of microstructure architecture, however, is a difficult task due to the microstructure of the electrospun being highly sensitive to the electrospinning parameters. One way to manipulate the microstructure architecture is by governing the process parameter and the knowledge in developing electrospinning machines brings the potential to develop novel electrospun scaffolds. This thesis focuses on the design and fabrication of the electrospinning machine. The machine was used to produce gelatin nanofibers with tailored microstructures and functionally graded multilayers. First, an electrospinning machine consists a high voltage supply, a syringe pump and a collector was built to produce homogeneous electrospun scaffolds. Gelatin and Polycaprolactone were spun into porous fibrous networks. The relationship between process parameters and microstructures was studied. These process parameters and microstructure dataset were used to produce the functionally graded multilayer electrospun gelatin scaffolds. A controllable moving stage was developed to precisely control the tip-collector distance and microstructure gradient over scaffold thickness. Microstructure images of functionally graded multilayers electrospun scaffold show the gradual changes of fiber diameters in nano-sized over the scaffold thickness. This study proposes a novel technique for designing the graded electrospun scaffolds which more closely mimic the native tissues.